Relationship between socioeconomic status and social network with loneliness: a cross-sectional study of China older adults with activity of daily living disabilities - Xin Cao; Luyao Niu; Wenjie Qu; Xinyu Ying; Ruyu Li; Xiyue Wang; Ruizhi Gao; Yuhua Chen; Yue-Xia Gao (BMJ Open)
Objectives The objective of this study is to explore the relationship between loneliness and socioeconomic status and social networks in older adults with activity of daily living (ADL) disabilities in China and investigate people who are more likely to feel lonely.Design Cross-sectional study.Setting This study was conducted in six districts of Nantong, Jiangsu, China.Participants A total of 880 older adults with ADL disabilities who participated in long-term care insurance and had an ADL score of less than 40 were investigated by the convenient sampling method.Primary outcome measures The UCLA Loneliness Scale (V.3) was used to assess loneliness.Results Among 880 participants, the mean age was 80.64 years (SD 10.29) and 59.43% were females. The mean score of loneliness was 44.70 (SD=10.01), and the majority suffered from moderate (39.89%) or moderate to severe (40.11%) loneliness. Regression showed that lower loneliness was associated with being females (β=−1.534, 95% CI: −2.841 to –0.228), married (β=−3.554, 95% CI: −4.959 to –2.149), often communicating with children (β=−3.213, 95% CI: −4.519 to –1.908), having more than two friends (β=−5.373, 95% CI: −6.939 to –3.808) and receiving home-based rehabilitation once a day (β=−3.692, 95% CI: −5.642 to –1.743). Participants who lived in rural areas (β=1.926, 95% CI: 0.658 to 3.193) and were unemployed before retirement (β=4.691, 95% CI: 1.485 to 7.898) experienced higher loneliness for older adults with ADL disability. The classification and regression tree model showed fewer friends and communication with children sometimes, and living in rural areas felt more lonely.Conclusions The poorer socioeconomic status and social network among older adults with ADL disability perceived more loneliness. Attention should be paid to the loneliness status of such vulnerable people, particularly those with ADL disabilities living in rural areas and having fewer social networks.